HBA1C (GLYCOSYLATED HEMOGLOBIN) DISCORDANCE IN ESTIMATING GLYCEMIC CONTROL - Choudhary, Sarita; Yadav, Charu; Vinayak, Kamini; Debnath, Ankana; Singhal, Ravi; Prakash, Anuj (International Journal of Pharma and Bio Sciences, 2026)
Glycated hemoglobin (HbA1c) is widely accepted as a standard biomarker for long-term glycemic control and prediction of diabetes-related complications; however, emerging clinical variables may influence its interpretation in routine practice. The present study was undertaken to evaluate the role and limitations of HbA1c measurement in the diabetic population and to analyse factors contributing to discrepancies in its reporting. This observational study included 100 whole blood samples collected from Medanta–The Medicity, Gurugram, India. Two milliliters of venous blood were collected in EDTA tubes, and HbA1c was estimated using High-Performance Liquid Chromatography (HPLC) on the Bio-Rad D100 analyser. Baseline HbA1c values were compared with repeat measurements obtained after an average follow-up period of 45 days. Correlation with blood glucose levels and associated comorbidities was also assessed. The study population had a mean age of 61 years. A statistically significant change in HbA1c levels was observed over the follow-up period (8.4% vs 8.1%, p = 0.04). Rapid availability of HbA1c results facilitated more frequent monitoring and influenced therapeutic decisions. However, clinically relevant discordance between HbA1c and glycemic status was noted in selected cases, highlighting potential analytical and biological interferences. These findings indicate that although HbA1c remains a valuable and reliable marker for monitoring glycemic control, its interpretation requires careful consideration of patient-specific factors and associated clinical conditions. Standard assessment norms may need contextual modification in selected scenarios to avoid misinterpretation and inappropriate treatment adjustments.